Magnetic calcium-iron layered double-metal hydroxide catalyst as well as preparation and application thereof
Through the combination technology of magnetic calcium-iron layered bimetallic hydroxide catalyst and activated persulfate, the problem of low efficiency and high cost in degrading SMX in water is solved, and an efficient, economical and environmentally friendly SMX degradation effect is achieved, and good catalyst recovery performance is provided.
Patent Information
- Application Number
- CN202411767968.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
Traditional biological treatment, adsorption and photocatalytic methods are inefficient, costly, and difficult to effectively apply in the natural environment when degrading sulfamethoxazole (SMX) in water, resulting in the persistent existence of SMX in the water environment, affecting the environment and public health.
The catalyst was prepared by hydrothermal method for efficient degradation of SMX in water by combining magnetic calcium-iron layered bimetallic hydroxide catalyst (CaFe-LDH@CuFe2O4) and activated persulfate (PMS).
It achieves efficient, economical and environmentally friendly SMX degradation. The catalyst has good separation and recovery capabilities, can maintain efficient degradation performance within different pH ranges, with a degradation efficiency of up to 94.48%, and the catalyst can be recycled and reused multiple times.
Abstract
Description
Technical Field
[0001] The invention relates to the fields of environmental engineering and water treatment, in particular to a magnetic calcium iron layered double metal hydroxide catalyst for efficiently degrading sulfamethoxazole in water through activated persulfate (PMS) and its preparation and application. Background Art
[0002] As a commonly used antibiotic, the widespread use of sulfamethoxazole (SMX) in various therapeutic applications has led to its ubiquity in aquatic environments, causing serious environmental and public health problems. The persistence of SMX in water bodies and the low efficiency of its degradation by traditional wastewater treatment pose a serious challenge. Studies have shown that traditional biological treatment methods often fail to effectively remove SMX, with removal rates usually below 50%. For example, a study by Schmidt et al. (2017) pointed out that despite the use of various biological processes, most of SMX remains unaffected due to its synthetic nature and resistance to biodegradation. Further studies have found that the persistence of SMX in water bodies not only increases the risk of bacterial resistance, but may also affect human health through the food chain. As shown by Larcher and Yargeau, SMX in water can be accumulated by aquatic organisms and transmitted to humans through the food chain, which may increase exposure to these drugs. In addition, although traditional adsorption and photocatalytic methods can degrade SMX to a certain extent, they often take a long time or rely on specific environmental conditions, and the cost is relatively high. For example, one study mentioned that although activated carbon adsorption can remove a portion of SMX, its regeneration process is complicated and costly. Similarly, although the photocatalytic method shows good results under laboratory conditions, its application in the natural environment is limited by the intensity and wavelength of light. In view of the above problems, it is particularly urgent to develop a new, economical and efficient technology to solve the pollution problem of SMX in the water environment. The magnetic calcium iron layered double metal hydroxide activation PMS technology of the present invention provides an effective solution through innovative material design and synthesis methods.
[0003] In the field of modified layered double hydroxides to activate PMS to degrade SMX, researchers have constructed a catalyst (SA-Co-LDH) in which single-atom Co is confined between the layers of layered double hydroxides (LDHs) to activate PMS. This catalyst has a good oxidative degradation effect on emerging organic pollutants (EOCs). Specifically, in the process of activating PMS to degrade SMX, it can selectively generate free radicals with a long life span, which promotes the degradation reaction. Professor Bian Zhaoyong's team used nanofiber Co3O4 and layered fluorine-free MXene (ff-Ti3C2Tx) to self-assemble to prepare nanofiber layered structure ff-Ti3C2Tx-Co3O4, which was used to activate PMS to degrade antibiotics. The material showed excellent performance in activating PMS to degrade antibiotics in the pH range of 4-10, with a degradation rate close to 100%, and was resistant to ion interference. The efficiency of removing SMX by the ff-Ti3C2Tx-Co3O4 membrane prepared by vacuum filtration remained above 95% within 900 minutes. Other researchers have used the melt-quenching method to convert ZIF-62(Co) rich in cobalt sites into ZIF-62(Co) glass (AG-ZIF-62(Co)), which has a certain correlation with layered double hydroxides and is used to activate PMS to degrade SMX in water. The performance of AG-ZIF-62(Co) glass in activating PMS to degrade SMX is not negatively affected by pH. In the presence of different anions, it has different effects on the degradation efficiency. For example, the presence of chloride ions induces the production of HClO, thereby improving the degradation efficiency, while some other anions have no obvious inhibitory effect. Some researchers have prepared magnetic magnesium-iron layered double hydroxides. Magnetic magnesium-iron layered double hydroxides were prepared by coprecipitation and other methods and used to activate PMS to degrade SMX. Due to its special structure and composition, it has good magnetic properties, is easy to recycle and reuse, and exhibits certain catalytic activity in activating PMS. Summary of the invention
[0004] The purpose of the present invention is to provide a magnetic calcium iron layered double metal hydroxide catalyst (CaFe-LDH@CuFe2O4) in order to improve the deficiencies of the prior art. Another purpose of the present invention is to provide a method for preparing the above catalyst. Another purpose of the present invention is to provide the application of the above catalyst in activating PMS to efficiently degrade SMX in water. The present invention has the advantages of simple operation, low cost, high degradation efficiency, etc.
[0005] A magnetic calcium iron layered double hydroxide (CaFe-LDH@CuFe2O4) catalyst, characterized in that the catalyst is composed of a carrier and a layered double hydroxide, wherein the layered double hydroxide is a calcium iron layered double hydroxide, and the carrier is a magnetic copper ferrite CuFe2O4; wherein the loading mass percentage of the catalyst Ca element is 8-16%, and the Ca3 + and Fe 2+ The molar ratio is (2-4):1.
[0006] The present invention also provides a method for preparing the above-mentioned magnetic calcium iron layered double metal hydroxide catalyst, and the specific steps are as follows:
[0007] (1) Preparation of magnetic copper ferrite CuFe2O4: dissolving copper salt and iron salt in ethylene glycol (EG) solution, adding anhydrous sodium acetate after the EG is completely dissolved, stirring at room temperature to dissolve and fully disperse the solution; after the stirring is completed, transferring the solution to a hydrothermal reactor for hydrothermal treatment; after the reaction is completed, cooling naturally, washing, and vacuum drying to obtain magnetic copper ferrite CuFe2O4;
[0008] (2) Preparation of CaFe-LDH@CuFe2O4: Weigh iron salt and calcium salt, dissolve them in water, and stir to mix them evenly; then add urea and stir until completely dissolved; add the magnetic copper ferrite product in step (1) to the solution, stir to mix evenly, transfer the mixed solution to a hydrothermal reactor, and perform a hydrothermal reaction at high temperature; after the reaction, cool naturally, wash the product, and then vacuum dry to obtain a magnetic calcium iron layered double hydroxide catalyst CaFe-LDH@CuFe2O4.
[0009] Preferably, the iron salt in step (1) is anhydrous ferric chloride or ferric chloride hexahydrate; the copper salt is copper chloride or copper chloride dihydrate; the molar ratio of the iron salt to the copper salt is (2-3):1; the volume ratio of the amount of the iron salt to the ethylene glycol is 0.02-0.04 mol·L -1 The volume ratio of anhydrous sodium acetate to ethylene glycol is 0.25 to 1 mol·L -1 ; The stirring time is 1 to 2 hours, and the rotation speed is 250 to 350 rpm; the hydrothermal reaction time is 10 to 14 hours, and the temperature is 160 to 180°C; the product cleaning process is to use deionized water and anhydrous ethanol to alternately clean until the pH value of the filtrate is 6.5 to 7.5; the vacuum drying temperature is 60 to 80°C, and the time is 10 to 14 hours.
[0010] Preferably, the calcium salt in step (2) is anhydrous calcium chloride or calcium chloride dihydrate; the iron salt is anhydrous ferric chloride or ferric chloride hexahydrate; the molar ratio of the calcium salt to the iron salt is (2-4):1; the volume ratio of the amount of the calcium salt to water is 0.2-0.4 mol·L -1 The volume ratio of urea to water is 0.5 to 1.5 mol·L -1 The ratio of the added mass of copper ferrite to the volume of water is 0.5 to 2 g·L -1; The stirring time is 1 to 2 hours, and the rotation speed is 250 to 350 rpm; the hydrothermal reaction time is 10 to 14 hours, and the temperature is 160 to 180°C; the cleaning process is to use deionized water to clean the filtrate until the pH value of the filtrate is 6.5 to 7.5; the vacuum drying temperature is 60 to 80°C, and the time is 10 to 14 hours.
[0011] The present invention also provides an application of the magnetic calcium iron layered double metal hydroxide catalyst in the degradation of sulfamethoxazole SMX in wastewater. The specific steps are: adding CaFe-LDH@CuFe2O4 catalyst and PMS to simulated SMX wastewater, placing it in a constant temperature shaking bed for shaking reaction; wherein the pH of the simulated SMX wastewater is adjusted to 2.00-12.00, and the SMX concentration is 10-40 mg·L -1 , the PMS addition concentration is 1.00-2.00 mM, and the volume ratio of the catalyst addition mass to the wastewater is 0.5-2 g·L -1 The speed of the shaking bed was set to 150-250 rpm, and the shaking reaction was carried out at 20-55°C for 1-3 hours.
[0012] Beneficial effects:
[0013] (1) The catalyst of the present invention is green and environmentally friendly, can be synthesized on a large scale, can be recycled and reused, and has high economic benefits.
[0014] (2) Introduction of magnetic materials: The introduction of CuFe2O4 enhances the separation and recovery capabilities of the catalyst, solving the problem of secondary pollution caused by the difficulty in separating and recovering powdered layered double hydroxide catalysts in aqueous solution. At the same time, the adsorbent after the catalytic reaction can be recycled multiple times after simple regeneration.
[0015] (3) Synergistic effect: The multi-metal synergistic effect between CuFe2O4 and CaFe-LDH not only increases the dispersibility of LDH nanoparticles on the carrier CuFe2O4 and improves the degradation efficiency of SMX, but also overcomes the problem of limited ability of single LDH to activate PMS and low catalytic efficiency.
[0016] (4) The catalyst preparation process of the present invention is simple, the reaction conditions and process are easy to control, and the operation is convenient. DETAILED DESCRIPTION
[0017] In order to better understand the present invention, the present invention is further described below by way of examples, which are only used for explanation and do not constitute any limitation to the present invention.
[0018] Embodiment 1:
[0019] (1) Prepare simulated wastewater containing SMX, with an SMX concentration of 10 mg·L -1, the pH was adjusted to 2 using 0.1 M NaOH and HCl.
[0020] (2) Preparation of catalyst, the steps are as follows:
[0021] (a) Preparation of magnetic copper ferrite: Weigh 0.27g of CuCl2 (0.002mol) and 0.65g of FeCl3·6H2O (0.004mol) respectively, dissolve them in 100ml of ethylene glycol (EG) solution, add 2.065g (0.025mol) of anhydrous sodium acetate after they are completely dissolved, and stir mechanically at room temperature to dissolve and fully disperse them. The stirring time is 2h and the speed is 250rpm. After stirring, transfer the above solution to a hydrothermal reactor for hydrothermal treatment. The reaction time is 14h and the temperature is 170℃. Use deionized water and anhydrous ethanol to wash alternately several times until the filtrate is neutral (pH=6.5). The washed product is placed in a vacuum environment and dried at 60℃ for 12h to obtain magnetic copper ferrite (CuFe2O4).
[0022] (b) Preparation of CaFe-LDH@CuFe2O4: 2.2196g CaCl2 (0.02mol) and 1.625g FeCl3 (0.01mol) were weighed and dissolved in 100ml pure water, and mechanically stirred for 2h at a speed of 250rpm to completely dissolve and mix. Then 3.003g (0.05mol) urea was weighed and added to the above metal solution, and continued to stir for 2h until it was completely dissolved. Then 0.05g of CuFe2O4 dried in step (a) was added to the above solution and stirred at 250rpm for 2h to completely mix. Finally, the mixed solution was transferred to a 250ml hydrothermal reactor and hydrothermally treated at 160℃ for 14 hours. After the reaction was completed, it was cooled naturally, the product was taken out, and washed with deionized water until the pH was 6.5. Finally, the washed product was vacuum dried at 60℃ for 14h to obtain CaFe-LDH@CuFe2O4. The Ca element loading mass percentage in the catalyst is 8.26%.
[0023] (3) Weigh 0.05 g of the composite adsorbent CaFe-LDH@CuFe2O4 prepared in this embodiment, measure 100 ml of the SMX-containing simulated wastewater prepared in step (1), put CaFe-LDH@CuFe2O4 into the simulated wastewater, add 1.0 mM PMS, and react at a constant temperature of 25°C for 180 min at a shaking speed of 150 rpm. High performance liquid chromatography was used to detect the SMX concentration. When the pH was 2, the SMX removal rate was 94.48%. The catalyst was recovered and reused. It was reused 5 times under the same conditions, and the removal rate was 89.74%.
[0024] Embodiment 2:
[0025] (1) Prepare simulated wastewater containing SMX, with an SMX concentration of 20 mg·L -1 , the pH was adjusted to 7 using 0.1 M NaOH and HCl.
[0026] (2) Preparation of catalyst, the steps are as follows:
[0027] (a) Preparation of magnetic copper ferrite: Weigh 0.27g of CuCl2 (0.002mol) and 0.975g of FeCl3·6H2O (0.006mol) respectively, dissolve them in 100ml of ethylene glycol (EG) solution, add 1.43g (0.05mol) of anhydrous sodium acetate after they are completely dissolved, and stir mechanically at room temperature to dissolve and fully disperse them. The stirring time is 1.5h and the speed is 300rpm. After stirring, transfer the above solution to a hydrothermal reactor for hydrothermal treatment. The reaction time is 12h and the temperature is 180℃. Use deionized water and anhydrous ethanol to wash alternately several times until the filtrate is neutral (pH=7). The washed product is placed in a vacuum environment and dried at 70℃ for 11h to obtain magnetic copper ferrite (CuFe2O4).
[0028] (b) Preparation of CaFe-LDH@CuFe2O4: 3.3294g CaCl2 (0.03mol) and 1.625g FeCl3 (0.01mol) were weighed and dissolved in 100ml pure water, and mechanically stirred for 1.5h at 300rpm to completely dissolve and mix. Then 6.006g urea (0.1mol) was weighed and added to the above metal solution, and continued to stir for 1.5h until it was completely dissolved. Then 0.1g of CuFe2O4 dried in step (a) was added to the above solution and stirred at 300rpm for 1.5h to completely mix. Finally, the mixed solution was transferred to a 250ml hydrothermal reactor and hydrothermally treated at 170℃ for 12h. After the reaction was completed, it was cooled naturally, the product was taken out, and washed with deionized water until the pH was 7.0. Finally, the washed product was vacuum dried at 70℃ for 12h to obtain CaFe-LDH@CuFe2O4. The Ca element loading mass percentage in the catalyst is 10.91%.
[0029] (3) Weigh 0.1 g of the composite adsorbent CaFe-LDH@CuFe2O4 prepared in this embodiment, measure 100 ml of the SMX-containing simulated wastewater prepared in step (1), put CaFe-LDH@CuFe2O4 into the simulated wastewater, add 2.0 mM PMS, and react at 35°C for 120 min at a constant temperature of 200 rpm. High performance liquid chromatography was used to detect the SMX concentration. When the pH was 7, the SMX removal rate was 96.17%. The catalyst was recovered and reused. It was reused 5 times under the same conditions, and the removal rate was 91.11%.
[0030] Example 3
[0031] (1) Prepare simulated wastewater containing SMX, with an SMX concentration of 40 mg·L -1 , the pH was adjusted to 12 using 0.1 M NaOH and HCl.
[0032] (2) Preparation of catalyst, the steps are as follows:
[0033] (a) Preparation of magnetic copper ferrite: Weigh 0.682g of CuCl2·2H2O (0.004mol) and 2.164g of FeCl3·6H2O (0.008mol) respectively, dissolve them in 100ml of ethylene glycol (EG) solution, add 8.26g (0.1mol) of anhydrous sodium acetate after they are completely dissolved, and stir mechanically at room temperature to dissolve and fully disperse them. The stirring time is 1h and the speed is 350rpm. After stirring, transfer the above solution to a hydrothermal reactor for hydrothermal treatment. The reaction time is 10h and the temperature is 190℃. Use deionized water and anhydrous ethanol to wash alternately several times until the filtrate is neutral (pH=7.5). The washed product is placed in a vacuum environment and dried at 80℃ for 10h to obtain magnetic copper ferrite (CuFe2O4).
[0034] (b) Preparation of CaFe-LDH@CuFe2O4: 5.8808g CaCl2·2H2O (0.04mol) and 2.705g FeCl3·6H2O (0.01mol) were weighed and dissolved in 100ml pure water, and mechanically stirred for 1h at a speed of 350rpm to completely dissolve and mix. Then 9.009g urea (0.15mol) was weighed and added to the above metal solution, and continued to stir for 1h until it was completely dissolved. Then 0.2g of CuFe2O4 dried in step (a) was added to the above solution and stirred at 350rpm for 1h to completely mix. Finally, the mixed solution was transferred to a 250ml hydrothermal reactor and hydrothermally treated at 180℃ for 10 hours. After the reaction was completed, it was cooled naturally, the product was taken out, and washed with deionized water until the pH was 7.5. Finally, the washed product was vacuum dried at 80℃ for 10h to obtain CaFe-LDH@CuFe2O4. The Ca element loading mass percentage in the catalyst is 15.82%.
[0035] (3) Weigh 0.2 g of the composite adsorbent CaFe-LDH@CuFe2O4 prepared in this embodiment, measure 100 ml of the simulated wastewater containing SMX prepared in step (1), put CaFe-LDH@CuFe2O4 into the simulated wastewater, add 2.0 mM PMS, and react at a constant temperature of 45°C for 60 min at a shaking speed of 250 rpm. High performance liquid chromatography was used to detect the SMX concentration. When the pH was 12, the SMX removal rate was 91.64%. The catalyst was recovered and reused. Under the same conditions, it was reused 5 times, and the removal rate was 86.67%.
Claims
1. A magnetic calcium iron layered double hydroxide catalyst, characterized in that The catalyst is composed of a carrier and a layered double metal hydroxide, wherein the layered double metal hydroxide is a calcium iron layered double metal hydroxide, and the carrier is magnetic copper ferrite CuFe2O4; wherein the loading mass percentage of the catalyst Ca element is 8-16%, and the Ca 3+ and Fe 2+ The molar ratio is (2-4):
1.
2. A method for preparing the magnetic calcium iron layered double hydroxide catalyst as claimed in claim 1, wherein the specific steps are as follows: (1) Preparation of magnetic copper ferrite CuFe2O4: dissolving copper salt and iron salt in ethylene glycol solution, adding anhydrous sodium acetate after the copper salt and iron salt are completely dissolved, stirring at room temperature to dissolve and fully disperse the solution; after the stirring is completed, transferring the solution to a hydrothermal reactor for hydrothermal treatment; after the reaction is completed, cooling naturally, washing, and vacuum drying to obtain magnetic copper ferrite CuFe2O4; (2) Preparation of CaFe-LDH@CuFe2O4: Weigh iron salt and calcium salt, dissolve them in water, and stir to mix them evenly; then add urea and stir until completely dissolved; add the magnetic copper ferrite product in step (1) to the solution, stir to mix evenly, transfer the mixed solution to a hydrothermal reactor, and perform a hydrothermal reaction at high temperature; after the reaction, cool naturally, wash the product, and then vacuum dry to obtain a magnetic calcium iron layered double hydroxide catalyst CaFe-LDH@CuFe2O4.
3. The method according to claim 2, characterized in that The iron salt in step (1) is anhydrous ferric chloride or ferric chloride hexahydrate; the copper salt is copper chloride or copper chloride dihydrate; the molar ratio of the iron salt to the copper salt is (2-3):1; the volume ratio of the amount of the iron salt to the ethylene glycol is 0.02-0.04 mol·L -1 The volume ratio of anhydrous sodium acetate to ethylene glycol is 0.25 to 1 mol·L -1 ; The stirring time is 1 to 2 hours, and the rotation speed is 250 to 350 rpm; the hydrothermal reaction time is 10 to 14 hours, and the temperature is 160 to 180°C; the product cleaning process is to use deionized water and anhydrous ethanol to alternately clean until the pH value of the filtrate is 6.5 to 7.5; the vacuum drying temperature is 60 to 80°C, and the time is 10 to 14 hours.
4. The method according to claim 2, characterized in that The calcium salt in step (2) is anhydrous calcium chloride or calcium chloride dihydrate; the iron salt is anhydrous ferric chloride or ferric chloride hexahydrate; the molar ratio of the calcium salt to the iron salt is (2-4):1; the volume ratio of the amount of the calcium salt to water is 0.2-0.4 mol·L -1 The volume ratio of urea to water is 0.5 to 1.5 mol·L -1 The ratio of the added mass of copper ferrite to the volume of water is 0.5 to 2 g·L -1 ; The stirring time is 1 to 2 hours, and the rotation speed is 250 to 350 rpm; the hydrothermal reaction time is 10 to 14 hours, and the temperature is 160 to 180°C; the cleaning process is to use deionized water to clean the filtrate until the pH value of the filtrate is 6.5 to 7.5; the vacuum drying temperature is 60 to 80°C, and the time is 10 to 14 hours.
5. Use of the magnetic calcium iron layered double hydroxide catalyst as claimed in claim 1 for degrading sulfamethoxazole SMX in wastewater.
6. The use according to claim 5, characterized in that The specific steps are as follows: add CaFe-LDH@CuFe2O4 catalyst and PMS to the simulated SMX wastewater, and place it in a constant temperature shaking bed for shaking reaction; wherein the pH of the simulated SMX wastewater is adjusted to 2.00-12.00, and the SMX concentration is 10-40 mg·L -1 , the PMS addition concentration is 1.00-2.00 mM, and the volume ratio of the catalyst addition mass to the wastewater is 0.5-2 g·L -1 The speed of the shaking bed was set to 150-250 rpm, and the shaking reaction was carried out at 20-55°C for 1-3 hours.
Citation Information
Patent Citations
Hydrotalcite-like compound-spinel type ferrite combined material and preparation method thereof
CN102430411A
Preparation method and application of copper ferrite nano material
CN114099677A
Modified copper-iron spinel catalyst as well as preparation method and application thereof
CN116393154A
Modified carbon-based calcium-iron layered double-metal hydroxide catalyst as well as preparation and application thereof
CN118743994A
Cited By
Method for degrading antibiotic wastewater based on SR-AOPs mediated Fenton system
CN120172532A